(untitled) (Trento Student Law Review, 2019)
A Low-Profit Limited Liability Company, or an L3C, is a dynamic entity that statutorily combines such competing characteristics as a social purpose and profit generation. Although not all states have statues allowing the creation of L3Cs, the entity has proven to be quite popular, especially in the non-for-profit and social enterprise arenas. Presently, there are about 1,000 of L3Cs in operation in the United States.1 This article discusses L3C entities which were specifically designed to increase the number of program-related investments that private foundations make to such social-purpose businesses.